Von Herzen! 200 Jahre Missa Solemnis - Schroeter-Wittke, Harald (Praktische Theologie)

A $C^k$-seeley-extension-theorem for Bastiani’s differential calculus - Hanusch, Maximilian (Canadian Journal of Mathematics)
Keywords: extension of differentiable maps

Beste Bedingungen für junge Ökonominnen und Ökonomen? Neue Daten und Empfehlungen der Arbeitsgruppe “Nachwuchs” im Verein für Socialpolitik - Bayer, Christian; Englmaier, Florian; Riphahn, Regina; Schmidt-Dengler, Philipp; Sondergeld, Virgina; Sureth-Sloane, Caren; von Wangenheim, Jonas; Weizsäcker, Georg (Perspektiven der Wirtschaftspolitik)
Der Verein für Socialpolitik hat zur Bearbeitung seines Schwerpunktthemas „Nachwuchs“ für die Dauer der Kalenderjahre 2021-2022 eine Arbeitsgruppe eingerichtet – im Folgenden: AG Nachwuchs –, deren Aufgabe das Vorlegen eines umfassenden Berichts zur Situation der VWL-Promovierenden und -PostDocs im DACH-Raum ist. Gestützt auf Datenerhebungen und strukturierte Interviews formuliert die AG Nachwuchs in diesem Bericht zwei Empfehlungen, jeweils eine für den Doc- und den PostDoc-Bereich. Sie empfiehlt im PostDoc-Bereich, dass die Fakultäten bzw. verwandte VWL-Einrichtungen den Übergang zu Tenure-Track beschleunigen und ihn durch eine systematische Planung der Zahlenverhältnisse zwischen den Karrierestufen bei ihrem wissenschaftlichen Personal begleiten. Dadurch sollen bessere Karriereperspektiven erreicht werden. Sowohl die befragten Nachwuchskräfte als auch die befragten Professor:innen und Programmleitungen betonen die Thematik der Stellenperspektiven stark. Im Doc-Bereich dokumentieren die Erhebungsdaten eine überraschend geringe Zufriedenheit der VWL-Promovierenden mit der Betreuungssituation durch die Professorenschaft. Die AG Nachwuchs empfiehlt daher eine höhere Betreuungsdichte und eine stärkere Vernetzung von Promovierenden. Weitere Hilfestellungen für Promovierende können in Mehrfach- oder Teambetreuungen sowie in der Bereitstellung von Informationen über die Vielfalt möglicher Karrierewege bestehen.

Development of a numerical simulation model for self-piercing riveting of additive manufactured AlSi10Mg - Heyser, Per; Petker, Rudolf; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
Laser additive manufacturing processes are used for the production of highly complex geometric structures due to their high geometric freedom. Additive manufacturing processes, in particular powder-based selective laser melting, are used to produce metallic additive manufactured components for the automotive and aerospace industries. Different materials are often joined together to realize sustainable lightweight construction. The production of such mixed construction joints is often realized using mechanical joining technology (e.g. self-piercing riveting). However, there is currently very little experience with the mechanical joining of metallic additive manufacturing components. Furthermore, there is insufficient knowledge about the effects that occur during the mechanical joining of additive manufacturing components. In this article, a method is presented to investigate the joinability of additively manufactured components with conventionally manufactured components using a numerical simulation of the self-piercing riveting process. For this purpose, the additive manufacturing materials are characterized experimentally, the simulation model is configured, and the joining process with additive manufacturing materials is represented in the numerical simulation. Furthermore, the influence of the building direction on the mechanical properties is shown using miniature tensile specimens. Besides the configuration of the simulation model, the influence of heat treatment on the self-piercing riveting process is presented.
Keywords: Mechanical Engineering; General Materials Science

Quantum space, ground space traversal, and how to embed multi-prover interactive proofs into unentanglement - Gharibian, Sevag; Rudolph, Dorian (14th Innovations in Theoretical Computer Science (ITCS))
Savitch's theorem states that NPSPACE computations can be simulated in PSPACE. We initiate the study of a quantum analogue of NPSPACE, denoted Streaming-QCMASPACE (SQCMASPACE), where an exponentially long classical proof is streamed to a poly-space quantum verifier. Besides two main results, we also show that a quantum analogue of Savitch's theorem is unlikely to hold, as SQCMASPACE=NEXP. For completeness, we introduce Streaming-QMASPACE (SQMASPACE) with an exponentially long streamed quantum proof, and show SQMASPACE=QMA_EXP (quantum analogue of NEXP). Our first main result shows, in contrast to the classical setting, the solution space of a quantum constraint satisfaction problem (i.e. a local Hamiltonian) is always connected when exponentially long proofs are permitted. For this, we show how to simulate any Lipschitz continuous path on the unit hypersphere via a sequence of local unitary gates, at the expense of blowing up the circuit size. This shows quantum error-correcting codes can be unable to detect one codeword erroneously evolving to another if the evolution happens sufficiently slowly, and answers an open question of [Gharibian, Sikora, ICALP 2015] regarding the Ground State Connectivity problem. Our second main result is that any SQCMASPACE computation can be embedded into "unentanglement", i.e. into a quantum constraint satisfaction problem with unentangled provers. Formally, we show how to embed SQCMASPACE into the Sparse Separable Hamiltonian problem of [Chailloux, Sattath, CCC 2012] (QMA(2)-complete for 1/poly promise gap), at the expense of scaling the promise gap with the streamed proof size. As a corollary, we obtain the first systematic construction for obtaining QMA(2)-type upper bounds on arbitrary multi-prover interactive proof systems, where the QMA(2) promise gap scales exponentially with the number of bits of communication in the interactive proof.

Isolating Personal Knowledge Spillovers: Coinventor Deaths and Spatial Citation Differentials - Balsmeier, Benjamin; Fleming, Lee; Lück, Sonja (American Economic Review: Insights)
We propose a new method to estimate and isolate the localization of knowledge spillovers due to the physical presence of a person, using after-application but pre-grant deaths of differently located coinventors of the same patent. The approach estimates the differences in local citations between the deceased and still-living inventors at increasingly distant radii. Patents receive 26 percent fewer citations from within a radius of 20 miles around the deceased, relative to still-living coinventors. Differences attenuate with time and distance, are stronger when still-living coinventors live farther from the deceased, and hold for a subsample of possibly premature deaths. (JEL O31, O33, O34, R32)
Keywords: Management; Monitoring; Policy and Law; Geography; Planning and Development

Dynamic conditioning of two particle discrete-time quantum walks - Pegoraro, Federico; Held, Philip; Barkhofen, Sonja; Brecht, Benjamin; Silberhorn, Christine (Physica Scripta)
In real photonic quantum systems losses are an unavoidable factor limiting the scalability to many modes and particles, restraining their application in fields as quantum information and communication. For this reason, a considerable amount of engineering effort has been taken in order to improve the quality of particle sources and system components. At the same time, data analysis and collection methods based on post-selection have been used to mitigate the effect of particle losses. This has allowed for investigating experimentally multi-particle evolutions where the observer lacks knowledge about the system's intermediate propagation states. Nonetheless, the fundamental question how losses affect the behaviour of the surviving subset of a multi-particle system has not been investigated so far. For this reason, here we study the impact of particle losses in a quantum walk of two photons reconstructing the output probability distributions for one photon conditioned on the loss of the other in a known mode and temporal step of our evolution network. We present the underlying theoretical scheme that we have devised in order to model controlled particle losses, we describe an experimental platform capable of implementing our theory in a time multiplexing encoding. In the end we show how localized particle losses change the output distributions without altering their asymptotic spreading properties. Finally we devise a quantum civilization problem, a two walker generalisation of single particle recurrence processes.

Konzeptentwicklung für ein Stahlbatteriegehäuse unter besonderer Berücksichtigung der Fügetechnik und des Korrosionsschutzes - Schmolke, Tobias; Meschut, Gerson; Spohr, Sebastian; Eckstein, Lutz; Brunner-Schwer, Christian; Rethmeier, Michael; Nothhelfer-Richter, Rolf; Hilt, Michael

Leak Tightness of Bonded Joints in Battery Housings Under Mechanical and Corrosive Loads - Schmolke, Tobias; Meschut, Gerson

Interaktive Einkaufserlebnisse in Innenstädten

Projekt FLEMING – Predictive Maintenance von zentralen Komponenten des Mittelspannungsnetzes - zur Heiden, Philipp (DASC-PM v1.1 Fallstudien)

Frauensache(n)? Mode und Gender aus feministischer Perspektive. - Haller, Melanie (Tietze, Katharina/Schnittler, Anna-Brigitta: Mode und Gender.)

Der Tod und die Liebe: Die Metaphysik der Kommunikation - Fuchs, Christian (Soziale Ordnungen des Sterbens: Theorie, Methodik und Einblicke in die Vergänglichkeit)

Digital Ethics. Media, Communication and Society Volume Five - Fuchs, Christian

Lebensdauerprognose für Stahlklebverbindungen bei multiaxialer Belastung mit Phasenverschiebung, veränderlicher Mittelspannung und variablen Amplituden - Nagel, Christof; Carillo Beber, Vinicius; Mayer, Bernd; Köster, Christian; Matzenmiller, Anton; Hecht, Matthias; Baumgartner, Jörg; Melz, Tobias; Tews, Karina; Çavdar, Serkan; Meschut, Gerson (23. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Experimental investigation of the fatigue behavior and calculation of the service life of adhesively bonded joints - Tews, Karina; Teutenberg, Dominik; Meschut, Gerson

Nonlinear S-Parameter Behavioral Model of a Photonic Radar Transceiver Chipset for Automotive Applications - Kruse, Stephan; Schwabe, Tobias; Kneuper, Pascal; Meinecke, Marc-Michael; Kurz, Heiko G.; Scheytt, J. Christoph
This paper presents a method to model monolithically integrated photonic radar transceiver (TRX) with optical local oscillator (LO) distribution in silicon germanium (SiGe) electronic photonic integrated circuits (EPICs). The model proposed approximates the behavior of the nonlinear scattering (S)-parameters and noise figure of each building block of the TRX chipset by Laplace polynomials and hyperbolic tangent functions. The modular approach of the model allows to optimize hardware components with respect to the entire TRX system, and fault identification with reduced computational effort. The proposed method is validated using the first monolithically integrated photonic radar transceiver chipset and shows excellent agreement with the post layout simulation results and, including the photodiode (PD) bandwidth (BW) degradation, also with the measurements.

Der digitale Kapitalismus. Arbeit, Entfremdung und Ideologie im Informationszeitalter - Fuchs, Christian

Experimental and numerical investigation of the damping properties of adhesively bonded tubular steel joints - Göddecke, Johannes; Meschut, Gerson; Damm, Jannis; Albiez, Matthias; Ummenhofer, Thomas; Kötz, Fabian; Matzenmiller, Anton (The Journal of Adhesion)

On the structure of regularization paths for piecewise differentiable regularization terms - Gebken, Bennet; Bieker, Katharina; Peitz, Sebastian (Journal of Global Optimization)
Regularization is used in many different areas of optimization when solutions are sought which not only minimize a given function, but also possess a certain degree of regularity. Popular applications are image denoising, sparse regression and machine learning. Since the choice of the regularization parameter is crucial but often difficult, path-following methods are used to approximate the entire regularization path, i.e., the set of all possible solutions for all regularization parameters. Due to their nature, the development of these methods requires structural results about the regularization path. The goal of this article is to derive these results for the case of a smooth objective function which is penalized by a piecewise differentiable regularization term. We do this by treating regularization as a multiobjective optimization problem. Our results suggest that even in this general case, the regularization path is piecewise smooth. Moreover, our theory allows for a classification of the nonsmooth features that occur in between smooth parts. This is demonstrated in two applications, namely support-vector machines and exact penalty methods.

Weaker Quadriceps Corticomuscular Coherence in Individuals Following ACL Reconstruction during Force Tracing - Sherman, David A.; Baumeister, Jochen; Stock, Matt S.; Murray, Amanda M.; Bazett-Jones, David M.; Norte, Grant E. (Medicine & Science in Sports & Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

The Mode of Endurance Exercise Influences Changes in EEG Resting State Graphs among High-Level Cross-Country Skiers. - Büchel, Daniel; Torvik, PØ; Lehmann, Tim; Sandbakk, Ø; Baumeister, Jochen (Med Sci Sports Exerc)

Inhibition of Motor Planning and Response Selection after Anterior Cruciate Ligament Reconstruction. - Sherman, DA; Baumeister, Jochen; Stock, MS; Murray, AM; Bazett-Jones, DM; Norte, GE (Med Sci Sports Exerc)

Numerical study of light backscattering from layers of absorbing irregular particles larger than the wavelength - Alhaddad, Samer; Förstner, Jens; Grynko, Yevgen (Journal of Quantitative Spectroscopy and Radiative Transfer)
Keywords: tet_topic_scattering

LoRa Transceiver for Load Monitoring and Control System in Microgrids - Mwammenywa, Ibrahim; Petrov, Dmitry; Holle, Philipp; Hilleringmann, Ulrich (2022 International Conference on Engineering and Emerging Technologies (ICEET))

Adorno and the Media in Digital Capitalism - Fuchs, Christian (Adorno und die Medien: Kritik, Relevanz, Ethik)

Recommendations for managing AI-driven change processes: when expectations meet reality - Stieglitz, Stefan; Möllmann, Nicholas R.J.; Mirbabaie, Milad; Hofeditz, Lennart; Ross, Björn (International Journal of Management Practice)
Artificial intelligence (AI) has moved beyond the planning phase in many organisations and it is often accompanied by uncertainties and fears of job loss among employees. It is crucial to manage employees attitudes towards the deployment of an AI-based technology effectively and counteract possible resistance behaviour. We present lessons learned from an industry case where we conducted interviews with affected employees. We evaluated derived resistance to AI factors in a large-scale (N = 368) survey and found that the deployment of AI-based technologies does not differ from other IT, but that the change is perceived differently due to misguided expectations.

Characterizing Ion Transport in Electrolytes via Concentration and Velocity Profiles - Mistry, Aashutosh; Srinivasan, Venkat; Steinrück, Hans-Georg (Advanced Energy Materials)
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment

Experimental Investigations of Carbon Fiber Reinforced Polymer Composites and Their Constituents to Determine Their Elastic Material Properties and Complementary Inhomogeneous Experiments with Local Strain Considerations - Penner, Eduard; Caylak, Ismail; Mahnken, Rolf (Fibers and Polymers)
Abstract Composite materials, such as fiber reinforced polymers, become increasingly important due to their excellent mechanical and lightweight properties. In this respect, this paper reports the characterization of a unidirectional carbon fiber reinforced polymer composite material. Particularly, the mechanical behavior of the overall composite and of the individual constituents of the composite is investigated. To this end, tensile and shear tests are performed for the composite. As a result, statistics for five transversely isotropic material parameters can be established for the composite. For the description of the mechanical properties of the constituents, tensile tests for the carbon fiber as well as for the polymer matrix are carried out. In addition, the volume fraction of fibers in the matrix is determined experimentally using an ashing technique and Archimedes’ principle. For the Young’s modulus of the fiber, the Young’s modulus and transverse contraction of the matrix, as well as the volume fraction of the constituents, statistics can be concluded. The resulting mechanical properties on both scales are useful for the application and validation of different material models and homogenization methods. Finally, in order to validate the obtained properties in the future, inhomogeneous tests were performed, once a flat plate with a hole and a flat plate with semicircular notches.
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Non-local integral-type damage combined to mean-field homogenization methods for composites and its parallel implementation - Lenz, Peter; Mahnken, Rolf (Composite Structures)
Keywords: Civil and Structural Engineering; Ceramics and Composites

Student Teachers ’ Knowledge of Congruence before a University Course on Geometry - Hoffmann, Max; Biehler, Rolf (Proceedings of the Fourth Conference of the International Network for Didactic Research in University Mathematics (INDRUM 2022, 19-22 October 2022))
Keywords: Teaching and learning of specific topics in university mathematics; Transition to; across and from university mathematics; Student Teachers; Geometry; Congruence; Double Discontinuity.

Innovations in university teaching based on mathematic education research - Florensa, Ignasio; Hoffmann, Max; Romo Vázquez, Avenilde; Zandieh, Michelle; Martínez-Planell, Rafael (Proceedings of the Fourth Conference of the International Network for Didactic Research in University Mathematics (INDRUM 2022, 19-22 October 2022))

Beep-and-Sleep: Message and Energy Efficient Set Cover - Götte, Thorsten; Kolb, Christina; Scheideler, Christian; Werthmann, Julian (Theor. Comput. Sci.)

Three-dimensional dipole momentum analog based on L-shape metasurface - Li, Tianyou; Chen, Yanjie; Wang, Yongtian; Zentgraf, Thomas; Huang, Lingling (Applied Physics Letters)
The achievement of a flat metasurface has realized extraordinary control over light–matter interaction at the nanoscale, enabling widespread use in imaging, holography, and biophotonics. However, three-dimensional metasurfaces with the potential to provide additional light–matter manipulation flexibility attract only little interest. Here, we demonstrate a three-dimensional metasurface scheme capable of providing dual phase control through out-of-plane plasmonic resonance of L-shape antennas. Under circularly polarized excitation at a specific wavelength, the L-shape antennas with rotating orientation angle act as spatially variant three-dimensional tilted dipoles and are able to generate desire phase delay for different polarization components. Generalized Snell's law is achieved for both in-plane and out-of-plane dipole components through arranging such L-shape antennas into arrays. These three-dimensional metasurfaces suggest a route for wavefront modulation and a variety of nanophotonic applications.
Keywords: Physics and Astronomy (miscellaneous)

Supporting Construction and Architectural Visualization through BIM and AR/VR: A Systematic Literature Review - Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (Proceedings of the 19th IFIP TC13 International Conference on Human-Computer Interaction (INTERACT 2023))

Learning Permutation-Invariant Embeddings for Description Logic Concepts - Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (Advances in Intelligent Data Analysis XXI: 21st International Symposium on Intelligent Data Analysis, IDA 2023, Louvain-la-Neuve, Belgium, April 12–14, 2023, Proceedings)
Keywords: dice enexa sail SFB-TRR 318 demir ngonga

Integrating Prospective Scenarios in Life Cycle Engineering: Case Study of Lightweight Structures - Ostermann, Moritz; Grenz, Julian; Triebus, Marcel; Cerdas, Felipe; Marten, Thorsten; Tröster, Thomas; Herrmann, Christoph (Energies)
Lightweight design is a common approach to reduce energy demand in the use stage of vehicles. The production of lightweight materials is usually associated with an increase in energy demand, so the environmental impacts of lightweight structures need to be assessed holistically using a life cycle assessment. To estimate the life cycle environmental impacts of a product in its developmental stage, for example, by life cycle engineering, future changes in relevant influencing factors must be considered. Prospective life cycle assessment provides methods for integrating future scenarios into life cycle assessment studies. However, approaches for integrating prospective life cycle assessment into product development are limited. The objective of this work is to provide the methodological foundation for integrating future scenarios of relevant influencing factors in the development of lightweight structures. The applicability of the novel methodology is demonstrated by a case study of a structural component in a steel, aluminium, and hybrid design. The results show that appropriate decarbonisation measures can reduce the life cycle greenhouse gas emissions by up to 95 percent until 2050. We also found that shifts in the environmentally optimal design are possible in future scenarios. Therefore, the methodology and data provided contribute to improved decision-making in product development.
Keywords: Life Cycle Engineering; Life Cycle Assessment; Lightweight Design; Prospective LCA; Future-oriented LCA; Energy System; Material production; Sustainable production

Digitalität, Mediatisierung und Bildung - Megatrends aus medienpädagogischer Perspektive - Herzig, Bardo (Bildung und Digitalität. Analysen - Diskurse - Perspektiven)

Modellbildung und Modellnutzung in der Allgemeinen Didaktik - Herzig, Bardo (Pädagogische Rundschau. Sackgasse oder Meilenstein? Zur Sinnhaftigkeit von Modellbildungen in der Erziehungswissenschaft)

Kinderstärkende Pädagogik in der Grundschule im Kontext (post-)pandemischer Herausforderungen. Kennzeichen, Kritische Anfragen und Blinde Flecke. Vortrag an der Tagung: Was Resilienz stärkt. Chancen und Risiken eines immer populärer werdenden Konzepts. Pädagogische Hochschule Heidelberg. - Büker, Petra

KrafT: Bildungsdokumentation in der inklusiven Schule partizipativ gestalten. 9. Paderborner Grundschultag zum Thema: „Demokratie Lernen von Anfang an“. Online - Büker, Petra; Herding, Jana; Drexler, Leonie

Near-Term Effects of Short-Term Study Abroad: A Longitudinal Examination of Learner Perceptions - Müller, Mareike (Frontiers: The Interdisciplinary Journal of Study Abroad)
A relatively small body of research has been conducted on the near- and long-term effects of study abroad (SA) to date. This existing research suggests that SA effects on language skills tend to be volatile, while the impact on various aspects of learners’ personal, academic, and professional development may be longer-lasting. Yet, learner perspectives on the dynamics and durability of such effects, in particular in the context of short-term SA programs, remain largely unexplored. This study hence investigates the near-term impact of short-term SA programs as experienced by students within the first months and years following their sojourns. A qualitative case-study design is employed to examine the accounts of four American students of German, who studied abroad in Austria for four weeks and were interviewed repeatedly over a period of up to 40 months after their sojourns. The results suggest that, from the students’ perspective, many effects deteriorate in the near term, although the overall sojourn experience still appears influential. Abstract in German Nur wenige Forschungsvorhaben haben sich bislang den mittel- bis langfristigen Auswirkungen studentischer Auslandsaufenthalte gewidmet; die bisherige Datenlage deutet jedoch darauf hin, dass die Auswirkungen auf sprachliche Kompetenzen eher unbeständig sind, wohingegen die persönliche, studiums- und berufsbezogene Entwicklung der Lernenden länger von einem Auslandsaufenthalt beeinflusst wird. Die Dynamik und Beständigkeit derartiger Auswirkungen wurden jedoch kaum mit Blick auf kurze Auslandsaufenthalte (≤ acht Wochen) sowie aus der Perspektive der Studierenden erforscht, was die vorliegende Studie insbesondere hinsichtlich mittelfristiger Effekte fokussiert. Mittels eines qualitativen Fallstudiendesigns werden die Interviewdaten vier amerikanischer Deutschlernender untersucht, die sich vier Wochen in Österreich aufhielten und in einem Zeitraum von bis zu 40 Monaten nach ihrem Aufenthalt wiederholt befragt wurden. Die Ergebnisse zeigen, dass viele Auswirkungen eines solchen Aufenthalts aus studentischer Perspektive mittelfristig verblassen, auch wenn der Auslandsaufenthalt im Gesamten weiterhin als einflussreiche Erfahrung wahrgenommen wird.

Investigation of change in dispersive behaviour during adhesive curing in multi-layered structures - Zeipert, Henning; von Germeten, Christian; Friesen, Olga; Claes, Leander; Johannesmann, Sarah; Henning, Bernd (Fortschritte der Akustik - DAGA 2023)

Bestimmung der Volumenviskosität mittels akustischer Absorptionsmessung - Claes, Leander (Fortschritte der Akustik - DAGA 2023)

Characterization of adhesion strength using guided ultrasonic waves - Nicolai, Marcel; Zeipert, Henning; Lugovtsova, Yevgeniya; Bulling, Jannis; Johannesmann, Sarah; Prager, Jens; Henning, Bernd (Fortschritte der Akustik - DAGA 2023)

Professionalisierung für Digitale Bildung im Grundschulalter. Ergebnisse des Forschungsprojekts P³DiG
Durch Digitalisierung und Digitalität entstehen neue Fragestellungen für die formale und non-formale Bildung. Insbesondere die Professionalisierung von Lehrkräften und Fachpersonal steht durch die Dynamik der technologischen und kulturellen Entwicklungen vor weitreichenden Herausforderungen. Der vorliegende Band beschäftigt sich mit der Frage der Professionalisierung von Grundschullehrkräften und pädagogischen Fachkräften für eine Digitale Bildung im Grundschulalter und ist auf der Grundlage des BMBF-Projekts Primat des Pädagogischen in der Digitalen Grundbildung – Grundsatzfragen und Gelingensbedingungen in der Professionalisierung von pädagogischen Akteur:innen für Kinder im Grundschulalter, P3DiG, entstanden. Im ersten Teil des Sammelbandes werden Grundlagen der Professionalisierung für eine Digitale Grundbildung dargelegt. Im zweiten Teil werden die Ergebnisse des Projekts präsentiert. Dabei werden sowohl Professionalisierungsmodelle für eine Digitale Grundbildung als auch die Ergebnisse der im Projekt durchgeführten empirischen Untersuchungen zur Digitalen Grundbildung im Grundschulalter vorgestellt. Der Band kann damit als Grundlage für die Ausarbeitung von Professionalisierungskonzepten in Hochschulen, Seminaren und Weiterbildungseinrichtungen dienen und liefert Impulse für die weitere wissenschaftliche Auseinandersetzung.

Room-Temperature Electrical Field-Enhanced Ultrafast Switch in Organic Microcavity Polariton Condensates - De, Jianbo; Ma, Xuekai; Yin, Fan; Ren, Jiahuan; Yao, Jiannian; Schumacher, Stefan; Liao, Qing; Fu, Hongbing; Malpuech, Guillaume; Solnyshkov, Dmitry (Journal of the American Chemical Society (JACS))
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis

Circularly polarized electroluminescence from a single-crystal organic microcavity light-emitting diode based on photonic spin-orbit interactions - Jia, Jichao; Cao, Xue; Ma, Xuekai; De, Jianbo; Yao, Jiannian; Schumacher, Stefan; Liao, Qing; Fu, Hongbing (Nature Communications)
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Quantum-optical excitations of semiconductor nanostructures in a microcavity using a two-band model and a single-mode quantum field - Rose, Hendrik; Vasil'ev, A. N.; Tikhonova, O. V.; Meier, Torsten; Sharapova, Polina (Physical Review A)

Instabilities of Polymer Melt Suspensions under Uniaxial Extension (Poster) - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim

Examining the Measurement Invariance and Convergent Validity of the SSIS-SELb-Student in Austria and Germany. 44th Annual Conference of the International School Psychology Association (ISPA) 2023. - Anthony, Christopher J.; Yost, M; Howe, A; Schwab, Susanne; Hassani, Sepideh; Hellmich, Frank; Löper, Marwin Felix; Görel, Gamze

Experimentelle und numerische Untersuchung des Einflusses variabler Betriebstemperaturen auf das Trag- und Versagensverhalten struktureller Klebverbindungen unter Crashbelastung - Schmelzle, Lars; Mergheim, Julia; Possart, Gunnar; Striewe, Marius; Meschut, Gerson (23. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Analysis of temperature effect on strength and microstructure in friction induced recycling process (FIRP) - Borgert, Thomas; Homberg, Werner (Materials Research Proceedings)
Abstract. In order to reduce global energy consumption in production and industry along with the associated CO2 emissions, existing resources must be used more efficiently. This includes the energy-efficient and comprehensive recycling of a wide range of metals. Especially for the production of aluminium, there is a large potential for saving energy using efficient recycling processes. With regard to the recycling of aluminium studies have shown that solid-state recycling processes are significantly more efficient considering the used energy and resources compared to the conventional, smelting-metallurgical recycling process. In this paper, the direct and energy-efficient friction-induced recycling process (FIRP) based on the conform process is further described and analysed in terms of the temperature-property relationships. For this purpose, the influence of the processing temperature on the microstructure and properties of the recycled semi-finished products is investigated using the toll system that enables an ECAP forming. Specific sections of the (in theory) infinite, recycled semi-finished product are taken and analysed at different process temperatures of the solid state recycling process. Based on these sections, the properties in terms of mechanical hardness, strength, ductility and grain size are analysed and a degressive relationship between process temperature and mechanical hardness up to a temperature of 270 °C can be shown. Applying the Hall-Petch relationship, it is analysed whether there is a correlation between the strength and the microstructure in the form of the grain size.
Keywords: Recycling; Aluminium; Friction-Induced; Energy Efficiency

Writing as Narrative Resource in Therapeutic Settings: Diaries, Sketches, Notes - Mildorf, Jarmila; Ketteler, Daniel (Narrative and Mental Health Today: Reimagining Theory and Practice)

Narrative and Mental Health: Reimagining Theory and Practice

Untersuchung überlagerter Effekte von Druckverlust und Totvolumen durch Rekuperation am isobaren Expansionsmotor - Mügge, Nils; Kronberg, Alexander; Glushenkov, Maxim; Kenig, Eugeny Y. (Chemie Ingenieur Technik)
Die Wirtschaftlichkeit von Wärmemotoren wird maßgeblich durch die Rückführung von Wärme in Rekuperatoren beeinflusst. Beim isobaren Expansionsmotor vom Bush-Typ, einem Wärmemotor, welcher bereits mit Wärmequellen ab 60°C betrieben werden kann, steigt der thermische Wirkungsgrad durch den Einsatz von Rekuperatoren signifikant. Gleichzeitig wirken sich das Fluidvolumen des Wärmeübertragers sowie der beim Betrieb auftretende Druckverlust negativ auf den thermischen Wirkungsrad aus. In dieser Arbeit wird der Zusammenhang von Totvolumen, Druckverlust und Wärmerückgewinnung untersucht und Empfehlungen für den Betrieb von Rekuperatoren am isobaren Expansionsmotor gegeben.
Keywords: Isobarer Expansionsmotor; Dynamische Wärmeübertragungsmodellierung; Phasenwechsel; dichte Arbeitsmedien

Narratives and Mental Health: An Introduction - Mildorf, Jarmila; Punzi, Elisabeth; Singer, Christoph (Narrative and Mental Health: Reimagining Theory and Practice)

Investigation of the leak tightness of structural adhesive joints for use in battery housings considering mechanical and corrosive loads - Schmolke, Tobias; Teutenberg, Dominik; Meschut, Gerson (The Journal of Adhesion)

Boron‐Centered Lewis Superacid through Redox‐Active Ligands: Application in C−F and S−F Bond Activation - Köring, Laura; Stepen, Arne; Birenheide, Bernhard; Barth, Simon; Leskov, Maxim; Schoch, Roland; Krämer, Felix; Breher, Frank; Paradies, Jan (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Boron‐Centered Lewis Superacid through Redox‐Active Ligands: Application in C−F and S−F Bond Activation - Köring, Laura; Stepen, Arne; Birenheide, Bernhard; Barth, Simon; Leskov, Maxim; Schoch, Roland; Krämer, Felix; Breher, Frank; Paradies, Jan (Angewandte Chemie)
Keywords: General Medicine

Damping Properties of Bonded Structures Under Dynamic Loading - Göddecke, Johannes; Meschut, Gerson

Developing Quantitative Nondestructive Characterization of Nanomaterials: A Case Study on Sequential Infiltration Synthesis of Block Copolymers - Cara, Eleonora; Hönicke, Philipp; Kayser, Yves; Lindner, Jörg K. N.; Castellino, Micaela; Murataj, Irdi; Porro, Samuele; Angelini, Angelo; De Leo, Natascia; Pirri, Candido Fabrizio; Beckhoff, Burkhard; Boarino, Luca; et al. (ACS Applied Polymer Materials)
Keywords: Organic Chemistry; Polymers and Plastics; Process Chemistry and Technology

Experimental and simulative determination and correction of the effective gap extension in structured coaxial measuring systems - Josch, Sebastian; Jesinghausen, Steffen; Dechert, Christopher; Schmid, Hans-Joachim (Rheologica Acta)
Abstract The use of structured measuring systems to prevent wall slip is a common approach to obtain absolute rheological values. Typically, only the minimum distance between the measuring surfaces is used for further calculation, implying that no flow occurs between the structural elements. But this assumption is misleading, and a gap correction is necessary. To determine the radius correction $$Δ r$$ Δ r for specific geometries, we conducted investigations on three Newtonian fluids (two silicon oils and one suspension considered to be Newtonian in the relevant shear rate range). The results show that $$Δ r$$ Δ r is not only shear- and material-independent, but geometry-dependent, providing a Newtonian flow behaviour in a similar viscosity range. Therefore, a correction value can be determined with only minute deviations in different Newtonian fluids. As the conducted laboratory measurements are very time-consuming and expensive, a CFD-approach with only very small deviations was additionally developed and compared for validation purposes. Therefore, simulation is an effective and resource-efficient alternative to the presented laboratory measurements to determine $$Δ r$$ Δ r for the correction of structured coaxial geometries even for non-Newtonian fluids in the future.
Keywords: rheology; rheometry; suspension; coaxial; correction

Universities and Academic Labour in Times of Precarisation and Digitalisation - Allmer, Thomas

Towards reliable data-based optimal and predictive control using extended DMD - Schaller, Manuel; Worthmann, Karl; Philipp, Friedrich; Peitz, Sebastian; Nüske, Feliks (IFAC-PapersOnLine)
We present an approach for guaranteed constraint satisfaction by means of data-based optimal control, where the model is unknown and has to be obtained from measurement data. To this end, we utilize the Koopman framework and an eDMD-based bilinear surrogate modeling approach for control systems to show an error bound on predicted observables, i.e., functions of the state. This result is then applied to the constraints of the optimal control problem to show that satisfaction of tightened constraints in the purely data-based surrogate model implies constraint satisfaction for the original system.

Phase-preserving methods to visualise ultrasonic fields with schlieren imaging - Hetkämper, Tim; Koch, Kevin; Claes, Leander; Henning, Bernd (tm - Technisches Messen)
Keywords: Schlierentechnik

Towards an Amended Arm´s Length Principle - Tackling Complexity and Implementing Destination Rules in Transfer Pricing - Greil, Stefan; Overesch, Michael; Rohlfing-Bastian, Anna; Schreiber, Ulrich; Sureth-Sloane, Caren (Intertax)

Tailoring the directive nature of optical waveguide antennas - Farheen, Henna; Yan, Lok-Yee; Leuteritz, Till; Qiao, Siqi; Spreyer, Florian; Schlickriede, Christian; Quiring, Viktor; Eigner, Christof; Silberhorn, Christine; Zentgraf, Thomas; Linden, Stefan; Myroshnychenko, Viktor; et al. (Integrated Optics: Devices, Materials, and Technologies XXVII)
We demonstrate the numerical and experimental realization of optimized optical traveling-wave antennas made of low-loss dielectric materials. These antennas exhibit highly directive radiation patterns and our studies reveal that this nature comes from two dominant guided TE modes excited in the waveguide-like director of the antenna, in addition to the leaky modes. The optimized antennas possess a broadband nature and have a nearunity radiation efficiency at an operational wavelength of 780 nm. Compared to the previously studied plasmonic antennas for photon emission, our all-dielectric approach demonstrates a new class of highly directional, low-loss, and broadband optical antennas.
Keywords: tet_topic_opticalantenna

Optimized silicon antennas for optical phased arrays - Farheen, Henna; Strauch, Andreas; Scheytt, J. Christoph; Myroshnychenko, Viktor; Förstner, Jens (Integrated Optics: Devices, Materials, and Technologies XXVII)
We demonstrate a large-scale two dimensional silicon-based optical phased array (OPA) composed of nanoantennas with circular gratings that are balanced in power and aligned in phase, required for producing desired radiation patterns in the far-field. The OPAs are numerically optimized to have an upward efficiency of up to 90%, targeting radiation concentration mainly in the field of view. We envision that our OPAs have the ability of generating complex holographic images, rendering them an attractive candidate for a wide range of applications like LiDAR sensors, optical trapping, optogenetic stimulation and augmented-reality displays.
Keywords: tet_topic_opticalantenna

Bootstrapping the Open Science culture: The fellowship approach - Heck, Tamara; Steinhardt, Isabel; Rahal, Rima-Maria; Schubotz, Moritz; Scholl, Dominik; Behrens, Sarah (Research Ideas and Outcomes)
Keywords: Open Science

Possible points of blow-up in chemotaxis systems with spatially heterogeneous logistic source - Black, Tobias; Fuest, Mario; Lankeit, Johannes; Mizukami, Masaaki (Nonlinear Analysis: Real World Applications)
Keywords: Applied Mathematics; Computational Mathematics; General Economics; Econometrics and Finance; General Engineering; General Medicine; Analysis

Correction: Thermal influence of resistance spot welding on a nearby overmolded thermoplastic–metal joint - Wippermann, Jan; Meschut, Gerson; Koshukow, Wikentij; Liebsch, Alexander; Gude, Maik; Minch, Steven; Kolbe, Björn (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Förderung der sozialen Partizipation von Kindern im inklusiven Unterricht. Workshop auf dem 9. Paderborner Grundschultag. Thema: „Demokratie von Anfang an! Demokratie in der Grundschule erfahren, mitgestalten und reflektieren“ - Görel, Gamze; Hellmich, Frank; Löper, Marwin Felix

Reziprokes Peer-Tutoring zur Förderung von Schüler*innen mit Schwierigkeiten beim Mathematiklernen. - Vitt, Vivian; Häsel-Weide, Uta (Mathematica Didactica, 46)

Inklusive Praktiken unterrichtsintegrierter Förderung im Mathematikunterricht. - Häsel-Weide, Uta; Nührenbörger, M. (Mathematica Didactica, 46)

CDMA: Centrifugal Differential Mobility Analyzer - Ein Messprinzip zur Bestimmung von Multidimensionalen Partikeleigenschaften (Vortrag) - Rüther, Torben; Schmid, Hans-Joachim
Keywords: CDMA

Zur experimentellen Untersuchung der Reinstoffkondensation in Kissenplatten-Wärmeübertragern - Lutters, Nicole; Buckmann, Felix; Kenig, Eugeny Y.

Application of a new strategy for time-efficient laser treatment of galvanized steel substrates to improve the adhesion properties - Voswinkel, Dietrich (Journal of Manufacturing Processes)
Laser structuring to improve the adhesion properties of steel substrates in fiber-metal laminates offers many advantages that are highly suitable for modern industrial requirements. Maintenance and energy costs are relatively low, it is easy to automate, and there are no by-products such as chemicals or abrasives to dispose of or recycle. This makes laser structuring a particularly environmentally friendly process, which is nowadays more important than ever. On the other hand, the process time for laser structuring is much higher than for chemical pre-treatment, for example. In past studies, the time and cost efficiency of the laser structuring process has tended to play a minor role. However, there are approaches in which laser structured surfaces are adapted to the shear stress peaks occurring within the adhesive layer, thus requiring only partial structuring of the area to be bonded, potentially saving process time. In this experimental study, electrolytically galvanized steel substrates were partially laser structured to match the shear stress distribution and then bonded to a carbon fiber-reinforced plastic. The adhesion properties achieved were characterized using shear tensile tests and compared with the properties of the fully structured ones. With the partial laser structuring, a saving of 66 % of the conventional process time was achieved while maintaining 95 % of the same shear strength.
Keywords: Laser treatment Adhesive bonding Surface technology Hybrid materials

Musiklandschaften zwischen Rhein und Weser. Pluralisierung und Verflechtung entlang des Hellwegs in der Frühen Neuzeit. Unter Mitarbeit v. Markus Lauert

Computerunterstützte Strömungsuntersuchung von landwirtschaftlichen Abfällen - Bernemann, Sören Antonius; Maćkowiak, Jan; Maćkowiak, Jerzy; Kenig, Eugeny

Eliciting Security Requirements – An Experience Report - Trentinaglia, Roman; Merschjohann, Sven; Fockel, Markus; Eikerling, Hendrik (REFSQ 2023: Requirements Engineering: Foundation for Software Quality)

The Lax Equation and Weak Regularity of Asymptotic Estimate Lie Groups - Hanusch, Maximilian (Annals of Global Analysis and Geometry)
Keywords: Lax equation; generalized Baker-Campbell-Dynkin-Hausdorff formula; regularity of Lie groups

Numerical and Experimental Investigation of Twin-Roll Casting of Aluminum–Lithium Strips - Grydin, Olexandr; Garthe, Kai-Uwe; Yuan, Xueyang; Broer, Jette; Keßler, Olaf; Králík, Rostislav; Cieslar, Miroslav; Schaper, Mirko (Light Metals 2023)

On Cryptography Effects on Interconnect Reliability - Ghazal, Abdulkarim; Sadeghi-Kohan, Somayeh; Reimer, Jan Dennis; Hellebrand, Sybille
Keywords: WORKSHOP

Time-Optimal Model Predictive Control of Permanent Magnet Synchronous Motors Considering Current and Torque Constraints - Brosch, Anian; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Narrative Experiments with Medical Categorization and Normalization in B. S. Johnson's House Mother Normal - Strauß, Sara (Narrative and Mental Health)

Vergleichende Untersuchung der Wirkung verschiedener Mikrostrukturen auf die Flüssigkeitsausbreitung - Dechert, Christopher; Kengni Nkouemou, Augustin; Kenig, Eugeny Y.

How to suppress radiative losses in high-contrast integrated Bragg gratings - Hammer, Manfred; Farheen, Henna; Förstner, Jens (Journal of the Optical Society of America B)
High-contrast slab waveguide Bragg gratings with 1D periodicity are investigated. For specific oblique excitation by semi-guided waves at sufficiently high angles of incidence, the idealized structures do not exhibit any radiative losses, such that reflectance and transmittance for the single port mode add strictly up to one. We consider a series of symmetric, fully and partly etched finite gratings, for parameters found in integrated silicon photonics. These can act as spectral filters with a reasonably flattop response. Apodization can lead to more box shaped reflectance and transmittance spectra. Together with a narrowband Fabry–Perot filter, these configurations are characterized by reflection bands, or transmittance peaks, with widths that span three orders of magnitude.
Keywords: tet_topic_waveguide

Realization of a Multi-Output Quantum Pulse Gate for Decoding High-Dimensional Temporal Modes of Single-Photon States - Serino, Laura; Gil López, Jano; Stefszky, Michael; Ricken, Raimund; Eigner, Christof; Brecht, Benjamin; Silberhorn, Christine (PRX Quantum)
Keywords: General Physics and Astronomy; Mathematical Physics; Applied Mathematics; Electronic; Optical and Magnetic Materials; Electrical and Electronic Engineering; General Computer Science

Breathing in Manhattan: Carola Speads - The German Jewish Gymnastics Instructor Who Brought Mindfulness to America - Ribbat, Christoph

Experimental studies of the excitonic nonlinear response of GaAs-based type-I and type-II quantum well structures interacting with optical and terahertz fields - Meier, Torsten; Stein, M.; Schäfer, F.; Anders, D.; Littmann, J. H.; Fey, M.; Trautmann, Alexander; Ngo, C.; Steiner, J. T.; Reichelt, Matthias; Fuchs, C.; Volz, K.; et al. (Ultrafast Phenomena and Nanophotonics XXVII)
The nonlinear optical response of quantum well excitons is investigated experimentally using polarization resolved four wave mixing, optical-pump optical-probe, and optical-pump Terahertz-probe spectroscopy. The four-wave mixing data reveal clear signatures of coherent biexcitons which concur with straight-forward polarization selection rules at the Γ point. The type-I samples show the well-established time-domain beating signatures in the transients as well as the corresponding spectral signatures clearly. The latter are also present in type-II samples; however, the smaller exciton and biexciton binding energies in these structures infer longer beating times which, in turn, are accompanied by faster dephasing of the type-II exciton coherences. Furthermore, the THz absorption following spectrally narrow, picosecond excitation at energies in the vicinity of the 1s exciton resonance are discussed. Here, the optical signatures yield the well-established redshifts and blueshifts for the appropriate polarization geometries in type-I quantum well samples also termed “AC Stark Effect”. The THz probe reveals intriguing spectral features which can be ascribed to coherent negative absorption following an excitation into a virtual state for an excitation below the 1s exciton resonance. Furthermore, the scattering and ionization of excitons is discussed for several excitation geometries yielding control rules for elastic and inelastic quasiparticle collisions.

Terahertz-induced anomalous currents following the optical excitation of excitons in semiconductor quantum wells - Meier, Torsten; Ngo, C.; Priyadarshi, S.; Duc, H. T.; Bieler, M. (Ultrafast Phenomena and Nanophotonics XXVII)
Anomalous currents refer to electronic currents that flow perpendicularly to the direction of the accelerating electric field. Such anomalous currents can be generated when Terahertz fields are applied after an optical interband excitation of GaAs quantum wells. The underlying processes are investigated by numerical solutions of the semiconductor Bloch equations in the length gauge. Excitonic effects are included by treating the manybody Coulomb interaction in time-dependent Hartree-Fock approximation and additionally also carrier-phonon scattering processes are considered. The band structure and matrix elements are obtained from a 14-band k · p model within the envelope function approximation. The random phase factors of the matrix elements that appear due to the separate numerical diagonalization at each k-point are treated by applying a smooth gauge transformation. We present the macroscopic Berry curvature and anomalous current transients with and without excitonic effects. It is demonstrated that the resonant optical excitation of excitonic resonances can significantly enhance the Berry curvature and the anomalous currents.

Analysis of the nonlinear optical response of excitons in type-I and type-II quantum wells including many-body correlations - Meier, Torsten; Trautmann, Alexander; Stein, M.; Schäfer, F.; Anders, D.; Ngo, C.; Steiner, J. T.; Reichelt, Matthias; Chatterjee, S. (Ultrafast Phenomena and Nanophotonics XXVII)
The nonlinear optical response of quantum well excitons excited by optical fields is analyzed by numerical solutions of the semiconductor Bloch equations. Differential absorption spectra are computed for resonant pumping at the exciton resonance and the dependence of the absorption changes on the polarization directions of the pump and probe pulses is investigated. Coherent biexcitonic many-body correlations are included in our approach up to third-order in the optical fields. Results are presented for spatially-direct type-I and spatiallyindirect type-II quantum well systems. Due to the spatial inhomogeneity, in type-II structures a finite coupling between excitons of opposite spins exists already on the Hartree-Fock level and contributes to the absorption changes for the case of opposite circularly polarized pump and probe pulses.

Gain recovery dynamics in active type-II semiconductor heterostructures - Meier, Torsten; Schäfer, F.; Stein, M.; Lorenz, J.; Dobener, F.; Ngo, C.; Steiner, J. T.; Fuchs, C.; Stolz, W.; Volz, K.; Hader, J.; Moloney, J.V.; et al. (Applied Physics Letters)

Temporal sorting of optical multi-wave-mixing processes in semiconductor quantum dots - Meier, Torsten; Grisard, S.; Trifonov, A.V.; Rose, Hendrik; Reichhardt, R.; Reichelt, Matthias; Schneider, C.; Kamp, M.; Höfling, S.; Bayer, M.; Akimov, I.A (arxiv:2302.02480)

Entanglement of particles versus entanglement of fields: Independent quantum resources - Sperling, Jan; Agudelo, Elizabeth (Physical Review A)

Detector entanglement: Quasidistributions for Bell-state measurements - Sperling, Jan; Gianani, Ilaria; Barbieri, Marco; Agudelo, Elizabeth (Physical Review A)

Tracking Quantum Coherence in Polariton Condensates with Time-Resolved Tomography - Lüders, Carolin; Pukrop, Matthias; Barkhausen, Franziska; Rozas, Elena; Schneider, Christian; Höfling, Sven; Sperling, Jan; Schumacher, Stefan; Aßmann, Marc (Physical Review Letters)
Keywords: General Physics and Astronomy

Who benefits from quality competition in health care? A theory and a laboratory experiment on the relevance of patient characteristics - Brosig-Koch, Jeannette; Hehenkamp, Burkhard; Kokot, Johanna (Health Economics)
We study how competition between physicians affects the provision of medical care. In our theoretical model, physicians are faced with a heterogeneous patient population, in which patients systematically vary with regard to both their responsiveness to the provided quality of care and their state of health. We test the behavioral predictions derived from this model in a controlled laboratory experiment. In line with the model, we observe that competition significantly improves patient benefits as long as patients are able to respond to the quality provided. For those patients, who are not able to choose a physician, competition even decreases the patient benefit compared to a situation without competition. This decrease is in contrast to our theoretical prediction implying no change in benefits for passive patients. Deviations from patient-optimal treatment are highest for passive patients in need of a low quantity of medical services. With repetition, both, the positive effects of competition for active patients as well as the negative effects of competition for passive patients become more pronounced. Our results imply that competition can not only improve but also worsen patient outcome and that patients’ responsiveness to quality is decisive.
Keywords: physician competition; patient characteristics; heterogeneity in quality responses; fee-for-service; laboratory experiment

Price Regulation, Quality Competition and Location Choice with Costly Relocation - Hehenkamp, Burkhard; Kaarbøe, Oddvar M.
We consider a model where for-profit providers compete in quality in a price-regulated market that has been opened to competition, and where the incumbent is located at the center of the market, facing high costs of relocation. The model is relevant in markets such as public health care, education and schooling, or postal services. We find that, when the regulated price is low or intermediate, the entrant strategically locates towards the corner of the market to keep the incumbent at the low monopoly quality level. For a high price, the entrant locates at the corner of the market and both providers implement higher quality compared to a monopoly. In any case, the entrant implements higher quality than the incumbent provider. Social welfare is always higher in a duopoly if the cost of quality is low. For higher cost levels welfare is non-monotonic in the price and it can be optimal to the regulator not to use its entire budget. Therefore, the welfare effect of entry depends on the price and the size of the entry cost, and the regulator should condition the decision to allow entry on an assessment of the entry cost.
Keywords: Quality competition; Price regulation; Location choice; Product differentiation